Integrating mobile phones in English Language Teaching: a study in Manipur University - Singh, Irom Gambhir (Nepalese Linguistics, 2019)
The advancement of Information and Communication Technology (ICT) has great impact on students’ accessibility to information and different source materials. With the rapid development of modern science and technology, mobile devices have undergone massive changes and it has become so advanced that they can perform almost all the functions of a computer. Cell phones can be used for learning purposes. The present paper discusses possible future applications of cell phones for English language teaching and learning in Manipur University. The data was obtained from a set of questionnaires sent to selected students to find out their attitudes towards this mode of teaching English language. The analysis revealed that students use mobile phones to help them in their studies and they believe that integrating mobile phones in a language teaching gives the learners the opportunity of availing the benefits of digital age. They also believed that cell phones have great potential in language teaching and learning.